2019
DOI: 10.7249/rr2177
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Technology to Augment Clinical Care in Depression and Anxiety Disorders: An Evidence Map

Abstract: Limited Print and Electronic Distribution Rights This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…All but one of the studies included in this review reported a significant reduction in symptoms, which is similar to the vast majority observed by Ruelaz Maher et al (2019). One explanation for this overwhelmingly positive result is that technology was always added to clinical practice, which can already be expected to reduce symptoms to some degree.…”
Section: Symptom Changessupporting
confidence: 78%
See 1 more Smart Citation
“…All but one of the studies included in this review reported a significant reduction in symptoms, which is similar to the vast majority observed by Ruelaz Maher et al (2019). One explanation for this overwhelmingly positive result is that technology was always added to clinical practice, which can already be expected to reduce symptoms to some degree.…”
Section: Symptom Changessupporting
confidence: 78%
“…Second, what can researchers do to strengthen the evidence base for implementation? One recent evidence map examined the use of technology in randomized controlled trials (RCTs) targeting depression and anxiety among adults (Ruelaz Maher et al, 2019). Computer-based self-help was the most common intervention found, and the vast majority of studies included in the review had reported symptom improvement from baseline.…”
mentioning
confidence: 99%